Design And Development Of Hardware-In-The-Loop Test Equipment For Vehicle Instrument Cluster - Jamaludin, Wan Shahmisufi Wan (2019)
This research is about the design and development for Hardware-In-the-Loop (HIL) test equipment to evaluate the functionality of the Vehicle Instrument Cluster (VIC). The purpose of this test equipment is to generate a set of stimulus signals in order to display the corresponding output demonstrated in the VIC. Conventional solution provided by the Commercial-Off-The-Shelf Hardware-In-The-Loop Simulator (COTSHILS) is relatively expensive. It may contain unnecessary features and often non-extensible due to proprietary license which render the product to be less usable or scalable in the longer term. Hence, this test equipment is designed and developed from ground-up as the alternative solution capable to cater the industrial needs for product testing. Various signal are generated by this proposed test equipment which responsible to stimulate the display of VIC components such as Speedometer, Tachometer, Fuel Volume, and Engine Temperature and signal indicators of the VIC to be responsively displaying corresponding output. Test Jig Fixture is designed and fabricated to securely locate the VIC which is also the Device-Under-Test (DUT) before executing any test procedures. Experimental results had shown that the designs for frequency-based and resistance-based output has been improved compared to the methods of Tone Function and Preliminary Circuit, respectively. The mean of error for frequency generation has been improved up to 90.1% using AD9833 and SCC Module from 0.517 Hz error to 0.059 Hz, whilst the standard deviation of the error have increased by 88.89% from 1.004 Hz to 0.1044 Hz. The mean of error from the individual chart for the Fabricated PCB also had shown significant changes from 5.48 into 0.4391 which improved by 91.99%. The mean of error as shown in Moving Range also improved by 94.38% from 0.99 to 0.0556 BJT transistor is selected as the switching element of digital output generator for tell-tales, due to its capability of achieving faster rise time at 791.79 μs with the lowest cost of purchase at RM 1.62 per unit. In conclusion, this research has successfully designed and developed a HIL test equipment for VIC.